2020
DOI: 10.1002/aoc.5484
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization and evaluation of antimicrobial and cutaneous wound healing potentials of gold nanoparticles usingAllium saralicumR.M. Fritsch

Abstract: The use of herbal medicines dates back a long way in history. Herbal medicines have been widely used all over the world since ancient times and have been recognized by physicians and patients for their good therapeutic value as they have fewer adverse effects than modern medicines. Recently, researchers have used gold nanoparticles synthesized by plants in the prevention, control, and treatment of infectious disorders and cutaneous wounds. The aims of this study were to synthesize gold nanoparticles from aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Little data is available on the direct use of AuNPs prepared by green chemistry in the treatment of cutaneous candidiasis. Nevertheless, the results of this study are in line with those of the existing studies which indicated the antifungal effect of AuNPs [ 25 , 26 ]. Moreover, the results of this study were consistent with those of the previous studies which revealed that AuNPs bound to the Candida cell wall through electrostatic interactions and released reactive oxygen species that interfered with the signals between cells, caused cell damage, and induced apoptosis [ 3 ].…”
Section: Discussionsupporting
confidence: 92%
“…Little data is available on the direct use of AuNPs prepared by green chemistry in the treatment of cutaneous candidiasis. Nevertheless, the results of this study are in line with those of the existing studies which indicated the antifungal effect of AuNPs [ 25 , 26 ]. Moreover, the results of this study were consistent with those of the previous studies which revealed that AuNPs bound to the Candida cell wall through electrostatic interactions and released reactive oxygen species that interfered with the signals between cells, caused cell damage, and induced apoptosis [ 3 ].…”
Section: Discussionsupporting
confidence: 92%
“…The physical and chemical approaches have some disadvantages such as costly, require extensive labor, time consuming, utilizes harmful chemical reagents, use expensive instruments, complicated procedures, external additives, requires high temperature, and pressure, produced large quantity of waste that are toxic and hazardous to our ecosystem (Hu et al, 2020;Mohamed et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Different methods have been developed for the preparation of NPs such as chemical, physical and recently green chemistry or biological synthesis (Iqbal, Abbasi, Munir, Uddin, et al, 2020; Iqbal, Abbasi, Ahmad, Mahmoodi, et al, 2020; Ullah et al, 2020). The physical and chemical approaches have some disadvantages such as costly, require extensive labor, time consuming, utilizes harmful chemical reagents, use expensive instruments, complicated procedures, external additives, requires high temperature, and pressure, produced large quantity of waste that are toxic and hazardous to our ecosystem (Hu et al, 2020; Mohamed et al, 2019). The biological method is one of the methods uses bio‐based materials such as fungi, algae, and plants and is potentially being used for the production of NPs.…”
Section: Introductionmentioning
confidence: 99%
“…We next evaluated the particle size distribution of carriers, the peak of which lay in size from 6 to 10 nm. is size distribution was proved to be safe and devoid of toxicity in many literatures [20]. Moreover, the contacting surfaces became rough after the addition of AuNPs; the roughness has a positive effect on protein adsorption and cell adhesion.…”
Section: Characterization Of Cs/aunpsmentioning
confidence: 99%
“…But, controversy revolves around whether it is a direct contact or the release of gold ions. For a direct contact-killing mechanism, AuNPs adhere to the surface of bacterial cells by electrostatic interaction in the form of metallic gold which causes impaired cell membrane integrity, leakage of cell contents, and production of reactive oxygen species (ROS) [20]. For the gold-ion mediated mechanism, gold ions released tend to bind to thiol (sulfhydryl) groups of cellular lipoproteins to interfere with the respiratory chain and generate ROS.…”
Section: Introductionmentioning
confidence: 99%